2022
DOI: 10.1039/d2ma00816e
|View full text |Cite
|
Sign up to set email alerts
|

High performance NiOx nanoplatelet based films by a scrape-coating method for bifunctional electrochromic and energy storage devices

Abstract: Nickel oxide (NiOx) is considered a promising candidate for constructing complementary electrochromic devices with tungsten oxide. However, low electrochromic performance of NiO films has been a hindrance to its practical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Electrochromic smart windows can present different color response when different voltage was inputted, and it is attracting increasing interest for reducing the building energy consumption [58][59][60][61][62] . In comparison with rigid ECDs, flexible ECDs can be installed onto the pristine glass window without replacing all windows 63 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochromic smart windows can present different color response when different voltage was inputted, and it is attracting increasing interest for reducing the building energy consumption [58][59][60][61][62] . In comparison with rigid ECDs, flexible ECDs can be installed onto the pristine glass window without replacing all windows 63 .…”
Section: Introductionmentioning
confidence: 99%
“…Electrochromic smart windows can present different color responses when different voltages are applied and are attracting increasing interest in reducing energy consumption. [58][59][60][61][62] In contrast to rigid ECDs, flexible ECDs can be installed onto pristine glass windows without replacing them. 63 Moreover, they can be adapted to non-planar-shaped windows because of their intrinsic conforming ability.…”
Section: Introductionmentioning
confidence: 99%
“…A widely recognized and accepted point is that reactive oxygen species (ROS) derived from ozone conversion on oxygen (O) vacancies play an important role in catalytic toluene ozonation (CTO). Accordingly, a series of O-vacancy-enriched metal-based catalysts, including NiO x , , MnO x , , CuO x , PtO x , , and their derived composites, have been examined to achieve efficient CTO. Among these, nickel oxide (NiO) has received an enormous amount of attention due to its low cost, environmental friendliness, and excellent performance for CTO under mild conditions. , It is generally acknowledged that Ni vacancies, as a type of important Ruetschi defect, form easily on NiO surfaces and play a significant role in O-vacancy formation. , Accordingly, considerable efforts have been made to promote O-vacancy formation by regulating Ni vacancies in NiO catalysts via tuning the crystal structures, morphologies, and exposed crystal facets. ,, Among these, crystal facet engineering has been highlighted as a promising strategy because different crystal facets of NiO have their own atomic arrangement patterns and thus distinctive electronic structure, which is believed to result in differences in Ni vacancies and thus dramatically influence O-vacancy formation. For example, Tian’s group has found that cubic NiO with (100) facets possessed abundant Ni vacancies and thus promoted O-vacancy formation, which resulted in more ROS formation and thus facilitated CTO.…”
Section: Introductionmentioning
confidence: 99%